Stimulation of Trypanosoma cruzi adenylyl cyclase by an alpha D-globin fragment from Triatoma hindgut: effect on differentiation of epimastigote to trypomastigote forms. - Fraidenraich, D (1993)
A peptide from hindguts of the Triatoma hematophagous Chagas insect vector activates adenylyl cyclase activity in Trypanosoma cruzi epimastigote membranes and stimulates the in vitro differentiation of epimastigotes to metacyclic trypomastigotes. Hindguts were obtained from insects fed 2 days earlier with chicken blood. Purification was performed by gel filtration and HPLC on C18 and C4 columns. SDS/PAGE of the purified peptide showed a single band of about 10 kDa. The following sequence was determined for the 20 amino-terminal residues of this peptide: H2N-Met-Leu-Thr-Ala-Glu-Asp-Lys-Lys-Leu-Ile-Gln- Gln-Ala-Trp-Glu-Lys-Ala-Ala-Ser-His. This sequence is identical to the amino terminus of chicken alpha D-globin. On a Western blot, the peptide immunoreacted with a polyclonal antibody against chicken globin D. A synthetic peptide corresponding to residues 1-40 of the alpha D-globin amino terminus also stimulated adenylyl cyclase activity and promoted differentiation. This 125I-labeled synthetic peptide bound specifically to T. cruzi epimastigote cells. Activation of epimastigote adenylyl cyclase by the hemoglobin-derived peptide may play an important role in T. cruzi differentiation and consequently in the transmission of Chagas disease.